Cu(I)-thioether coordination complexes based on a chiral cyclic β-amino acid ligand - Jihee Lee; Jaewook Kim; Hongil Jo; Danim Lim; Jungwoo Hong; Jintaek Gong; Kang Min Ok; Hee-Seung Lee (Communications Chemistry, 2023)
Abstract Coordination complexes, particularly metalloproteins, highlight the significance of metal-sulfur bonds in biological processes. Their unique attributes inspire efforts to synthetically reproduce these intricate metal-sulfur motifs. Here, we investigate the synthesis and characterization of copper(I)-thioether coordination complexes derived from copper(I) halides and the chiral cyclic β-amino acid trans-4-aminotetrahydrothiophene-3-carboxylic acid (ATTC), which present distinctive structural properties and ligand-to-metal ratios. By incorporating ATTC as the ligand, we generated complexes that feature a unique chiral conformation and the capacity for hydrogen bonding, facilitating the formation of distinct geometric structures. Through spectroscopic analyses and density functional theory (DFT) calculations, we studied the complexes’ optical properties, including their emission bands and variable second-harmonic generation (SHG) efficiencies, which vary based on the halide used. Our findings underscore the potential of the ATTC ligand in creating unusual coordination complexes and pave the way for further investigations into their potential applications, particularly within materials science.